Wave‐induced changes in seaweed toughness entail plastic modifications in snail traits maintaining consumption efficacy. (9th March 2015) - Molis, Markus; Scrosati, Ricardo A.; El‐Belely, Ehab F.; Lesniowski, Thomas J.; Wahl, Martin; Heil, Martin
Summary Environmental stress can influence species traits and performance considerably. Using a seaweed–snail system from NW (Nova Scotia) and NE (Helgoland) Atlantic rocky shores, we examined how physical stress (wave exposure) modulates traits in the seaweed Fucus vesiculosus and indirectly in its main consumer, the periwinkle Littorina obtusata. In both regions, algal tissue toughness increased with wave exposure. Reciprocal‐transplant experiments showed that tissue toughness adjusted plastically to the prevailing level of wave exposure. Choice experiments tested the feeding preference of snails from sheltered, exposed and very exposed habitats for algae from such wave exposures. Snails from exposed and very exposed habitats consumed algal tissues at similar rates irrespective of the exposure of origin of the algae. However, snails from sheltered habitats consumed less algal tissues from very exposed habitats than tissues from sheltered and exposed habitats. Choice assays using reconstituted algal food (triturated during preparation) identified high thallus toughness as the explanation for the low preference of snails from sheltered habitats for algae from very exposed habitats. Ultrastructural analyses of radulae indicated that rachidian teeth were longest and the number of cusps in lateral teeth (grazing‐relevant traits) was highest in snails from very exposed habitats, suggesting that radulae are best suited to rupture tough algal tissues in such snails. No‐choice feeding experiments revealed that these radular traits were also phenotypically plastic, as they adjusted to the toughness of the algal food. Synthesis. This study indicates that the observed plasticity in the feeding ability of snails is mediated by wave exposure through phenotypic plasticity in the tissue toughness of algae. Thus, plasticity in consumers and their resource species may reduce the potential effects of physical stress on their interaction.